Hybrid Power System for a Fuel Station Considering Temperature Coefficient - Adedoja, Oluwaseye Samson; Babatunde, Damilola Elizabeth; Babatunde, Olubayo Moses (International Journal of Energy Economics and Policy, 2020)
It is crystal clear that appropriate technical sizing has a significant effect on the techno-economic analysis of an off-grid standalone energy system. As a result, this study presents the effect of incorporating the temperature coefficient in the optimal analysis of an off-grid hybrid system using a standard fuel (gas) station in Nigeria as a case study. Comparative analysis with and without the temperature coefficient was performed. The results showed that the inclusion of temperature coefficient leads to extra operation hours of the generator which will result in an increase in fuel consumption and annual operation cost of the diesel generator. Also, the initial cost of the PV/BAT/diesel is relatively higher than the diesel generator but, the generating emission of the hybrid system is lower when compared to the diesel-only which enhances the atmospheric condition of the society. Keywords: Techno-economic Analysis, Hybrid System, Temperature Coefficient, Fuel Consumption JEL Classifications: Q4, Q43 DOI: https://doi.org/10.32479/ijeep.9886